Faktor-Faktor Yang Mempengaruhi Sikap Ibu Melakukan Baby Spa Pada Bayi - Ni Putu Elga Kurniasari; I Ketut Alit Adianta; Ni Wayan Manik Parwati (Poltekkes Kemenkes Denpasar, 2019)
The optimal process of baby growth and development is very important to be considered to form quality and resilient human resources. There are many factors that influence the process of baby growthand development both internal and external factors. One of the external factors that really determines a baby's growth and development is stimulation to stimulate the development of brain cells and strengthen neurological correlation by doing baby spa. The aim of this research was to determine the factors that influence the attitude of a mothers to do baby spa on babiesat Ganesh JuniorMom Baby and Kids Care. This study employed cross sectional design. There were 37 respondents recruited as the sample through consecutive sampling technique. The data were collected using questionnaires and analyzed in univariate and bivariate by spearman’s rho and multivariate statistical tests using multiple linear regression tests. The findings indicated that the educational variable (sig 0.059) and availability of baby spa health resources (sig 0.658) were not significantly related; meanwhile, the knowledge variables (sig 0.033), beliefs (sig 0.011), family support (sig 0.002)related significantly to attitudeof mothers to do baby spa in babies and based on multiple linear regression tests family support was the dominant variable (sig 0.002).Keywords: Baby spa; family supports; knowledge; beliefs education; the availability of resources (baby spa clinic).